Developing WebQuest 2.0 model for promoting computational thinking skill - Diem Bui, Le; Gi Kim, Yong; Ho, Won; Thi Thu Ho, Ho; Khang Pham, Nguyen (International Journal of Engineering and Technology, 2018)
In this paper, we propose a new WebQuest model using Web 2.0 services to organize online learning activities by using OKMindmap for building WebQuest and suggest Scratch projects created by students for outcome. WebQuest is an inquiry-oriented lesson format in which most or all the information that learners work with comes from the web. WebQuests can be a valuable addition to a collaborative classroom. One of the goals is to increase critical thinking by employing higher levels of Bloom’s Taxonomy and Webb’s Depth of Knowledge. WebQuests can be a versatile tool for teaching students. OKMindmap is a useful, free, easy to use knowledge manipulation tool for content creation and management. It helps building an innovative collaborating environment for online class and provides a way to embed web service as a node. With this capability, any web service can be embedded as a node on a single map. Moreover, many users (about 40) can work on a same map together. Scratch is a free educational programming language that was developed by the Lifelong Kindergarten Group at the Massachusetts Institute of Technology (MIT) with over 21 million registered users and 25 million shared projects. Scratch is designed to be fun, educational, and easy to learn. It’s a programming language for all with the tools for creating interactive stories, games, art, simulations, and more, using block-based programming. Facebook is also used as a tool for connecting and sharing WebQuest with students. This model was experimented at the School of Education at Can Tho University, which brought us positive results through blended learning. Our desire is to build a WebQuest library in a simple, cost-effective way through this STEM-style education so that inservice and preservice teachers can share together for the best professional development during the current industrial revolution 4.0.